The “Zombi argument” against materialism: the foundations and perspectives of further investigation - Leonov, Andrii (Filosofska Dumka, 2017)
The paper deals with the main argument against the doctrine of Materialism and the heart of the mind-body problem — the Zombie argument. The main proponent of the idea of philosophical zombies is the Australian philosopher David Chalmers, whose main opus “The Conscious Mind” is wholly based on the idea of conceivability and logical possibility of zombies. The author aims to show that for the adequate analysis of Chalmers’ zombie argument, the frame of the Analytic philosophy alone is not sufficient, and due to that, one needs to involve Rene Descartes’ philosophy as well as Husserlian phenomenology. It is because the author considers Chalmers’ zombie argument as an inverted Cartesian argument from mind-body distinction and which has two levels of argumentation: intuitive obviousness and logical (conceivability-possibility frame). Chalmers’ appeal to phenomenal consciousness, experience and intuiton gives a solid basis to call his Philosophy of Mind project and himself as analytic phenomenology, and analytic phenomenologist respectively.